Analisis Kestabilan Lereng di Bukit Tui Section S0° 28’ 50.23” E100° 24’ 16.89”- S0° 28’ 49.19” E100° 24’ 17.07” Kecamatan Padang Panjang Barat Kota Padang Panjang - Yoszi Mingsi Anaperta; Eko Irwan (Universitas Negeri Padang, 2019)
Tui Hill is a limestone hill lined south of Padang Panjang, located between Rao-Rao Village to Tanah Hitam. The results of research at Tui Hill at the location S0° 28’ 50.23” E100° 24’ 16.89”- S0° 28’ 49.19” E100° 24’ 17.07” located in Tanah Hitam Village has a covered dolomite rock slope. Based on the Indonesian earthquake zoning map, the city of Padang Panjang is classified as a high earthquake vibration zone, ranging from 0.8-0.9 g. The potential for landslides on the slopes of the study can lead to the closure of the access road to dolomite mining so that it can hamper road user traffic and disrupt mining production as well as potential material losses and fatalities This study aims to determine the Safety Factors on earthquake slope research and recommendations to increase the value of Safety Factors (FK). Based on the results of the analysis by simulating earthquake vibration values the maximum earthquake vibration values that can be held by slopes in a safe condition is 0.2 g or equivalent to 6.4-6.6 on the Richter Scale, namely with FK of 1,281. Then, the author issued for the slope by changing the slope of the slope from 53˚ to 25˚ increases can obtain a slope FK value of 1.438, according to Joseph E. Bowles (1984) the slope is in accordance with the safe conditions.